DEVELOPMENT OF SCREENING METHOD FOR ALCOHOL USE DISORDER BASED ON ELECTROENCEPHALOGRAM ANALYSIS - PHAM , LAM VUONG (2016)
Chronic and heavy drinking alters level of neurotransmitters that may cause Alcohol Use Disorders (AUD) that includes both Alcohol Abuse (AA) and Alcohol Dependence (AD). Practically, AUD screening is based on subjective assessments that are highly subjective due to memory problems and dishonesty of AUD patients. We hypothesized that utilizing Electroencephalogram (EEG) can improve AUD screening. In accordance to the literature, it is evident that EEG based techniques may improve the efficiency ofAUD screening. However, there is still no such EEG study applying both for AA and AD.